How is the Relationship Between Learning Style, Self-Efficacy and Reading Comprehension? - Wulandari, Anggun; Sari, Artanti Puspita; Yukamana, Hanni (Yayasan Sembilan Pemuda Indonesia, 2023)
The research aims to understand the relationship between learning style, self-efficacy, and reading comprehension. This research was carried out at SMA N 4 Palembang of tenth-grade students. This research used a quantitative approach. Data testing techniques and questionnaires were used in this research. 63 students were given a multiple-choice reading comprehension test, a learning style questionnaire, and self – an efficacy questionnaire. Data testing techniques used in this research include normality tests, linearity tests, correlational analysis, simple regression analysis, and multiple regression analysis. The result of this study showed that 1) learning style did significantly correlate to reading comprehension, 2) self-efficacy did significantly correlate to reading comprehension, and 3) learning style, self-efficacy, and reading comprehension had a significant correlation. It was found that the R square was 0.045. It means that learning style and self-efficacy gave a 4.5% contribution to reading comprehension achievement. It could be concluded the correlation was at a medium level.